Photoprotective potential in some medicinal plants used to treat skin diseases in Sri Lanka. Issue 1 (December 2016) - Napagoda, Mayuri; Malkanthi, Benthota; Abayawardana, Subasinghe; Qader, Mohomed; Jayasinghe, Lalith
Abstract Background The constant exposure to solar ultraviolet radiation (UV) has a variety of harmful effects on human health. Although synthetic sunscreen products have been introduced as a preventive/therapeutic strategy, with the realization of their adverse side effects, the recent trend is to search for human friendly alternative formulations especially of plant origin. Therefore, the present study focuses on evaluation of photoprotective activity of aqueous extracts (1 mg/ml) of eleven medicinal plants in Sri Lanka that have been widely employed in traditional medicine as treatment options for various skin diseases and to improve the complexion. Methods For the determination of UV filtering potential of the extracts, UV absorption was measured and the sun protection factor (SPF) was calculated according the Mansur equation. The antioxidant activity was evaluated by DPPH and ABTS assays. Results Among the extracts, Atalantia ceylanica, Hibiscus furcatus, Leucas zeylanica, Mollugo cerviana, Olax zeylanica andOphiorrhiza mungos have displayed SPF value ≥ 25, which are even higher than two commercial photoprotective creams used as reference compounds.L. zeylanica andO. mungos have displayed a high UV absorbance in 260–350 nm range indicating their potential of being broad spectrum sunscreens. In addition, the extract ofO. mungos was found to be photostable, without any significant reduction in the SPF after exposure to direct solar radiation for 21 days. DPPH assay and the ABTS assay revealed that the extracts possess high antioxidant activity. Conclusion The results of the present study suggest that the presence of secondary metabolites with antioxidant property could be responsible for the high UV absorbance. Our findings would offer an exciting avenue for further research towards the development of herbal cosmetics.